2016
DOI: 10.1002/cbic.201600329
|View full text |Cite
|
Sign up to set email alerts
|

Helix‐Grafted Pleckstrin Homology Domains Suppress HIV‐1 Infection of CD4‐Positive Cells

Abstract: The size, functional group diversity and three-dimensional structure of proteins often allow these biomolecules to bind disease-relevant structures that challenge or evade small-molecule discovery. Additionally, folded proteins are often much more stable in biologically relevant environments, compared to their peptide counterparts. We recently showed that helix-grafted-display—extensive resurfacing and elongation of an existing solvent exposed helix in a Pleckstrin Homology (PH) domain—leads to a new protein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…[16] We next sought to evaluate sequence variability in the grafted helix. Five positions on Cpep-ELMO (Figure 2a) that bury into the C-peptide helix-binding cleft of N-peptide trimer (wild-type sequence WWIYI) were randomized by saturation mutagenesis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[16] We next sought to evaluate sequence variability in the grafted helix. Five positions on Cpep-ELMO (Figure 2a) that bury into the C-peptide helix-binding cleft of N-peptide trimer (wild-type sequence WWIYI) were randomized by saturation mutagenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Having demonstrated that some of our evolved C-peptide ELMO helix-grafted display proteins express better than Cpep-ELMO, retain helical structure, and bind to gp41 5-helix in vitro , we next measured their ability to suppress HIV infection using a live virus assay we have previously reported[16, 23]. In this method, HIV IIIB is administered to CD4+ mammalian cells stably integrated with a plasmid that encodes the HIV-1 long-terminal repeat (LTR) upstream of green fluorescent protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations